Seeing the Apocalypse: Essays on Bird Box - Grafius, Brandon R.; Stevenson, Gregory (University Press Copublishing Division, 2021)
Seeing the Apocalypse: Essays on Bird Box is the first volume to explore Josh Malerman’s best-selling novel and its recent film adaptation, which broke streaming records and became a cultural touchstone, emerging as a staple in the genre of contemporary horror. The essays in this collection offer an interdisciplinary approach to Bird Box, one that draws on the fields of gender studies, cultural studies, and disability studies. The contributors examine how Bird Box provokes questions about a range of issues including the human body and its existence in the world, the ethical obligations that shape community, and the anxieties arising from technological development. Taken together, the essays of this volume show how a critical examination of Bird Box offers readers a guide for thinking through human experience in our own troubled, apocalyptic times.